Characteristics of patients with non‐variceal upper gastrointestinal bleeding taking antithrombotic agents. Issue 1 (17th September 2014) - Yamaguchi, Daisuke; Sakata, Yasuhisa; Tsuruoka, Nanae; Shimoda, Ryo; Higuchi, Toru; Sakata, Hiroyuki; Fujimoto, Kazuma; Iwakiri, Ryuichi
<x xml:space="preserve">Abstract</x> Background and Aim The present study aimed to clarify the features and management of non‐variceal upper gastrointestinal bleeding (UGIB) in Japanese patients taking antithrombotic agents. Methods We retrospectively investigated the medical records of 560 patients who underwent emergency endoscopy for UGIB from 2002 to 2013. The patients were divided into two groups: group A, antithrombotic agent use; and group NA, no antithrombotic agent use. We compared clinical characteristics, comorbidities, and causes of UGIB between the groups. We also investigated management with antithrombotics. Results Of 560 patients with UGIB, 27.5% were taking antithrombotics, and this proportion gradually increased during the study period. Mean hemoglobin levels on admission were significantly lower in group A (8.0 ± 1.7 g/dL) than in group NA (8.9 ± 2.9 g/dL) (P < 0.001). Patients in group A developed more gastric ulcers and multiple ulcers than did patients in group NA. Incidence of Forrest Ia‐type bleeding was lower in group A than in group NA (P < 0.001), and the rate of endoscopic hemostasis was significantly higher in group A (98.7%) than in group NA (94.3%) (P = 0.022). After the release of the 2012 Japan Gastroenterological Endoscopy Society guidelines, the antithrombotic agent cessation periods were significantly shortened (P < 0.001). Conclusions Among patients with UGIB, those taking antithrombotics exhibited more severe clinical signs. However spurting hemorrhage was rare. Antithrombotics may be resumed early after endoscopic hemostasis.